Navarrian students in the Section of Universities of the Historical National Archive - Carmona de los Santos, María (Huarte de San Juan. Geografía e Historia, 2010)
The author explains the documentation preserved in the Universities Section of the National Historical Archive, identifying the different institutions which produced them (University of Alcalá, Noble Seminary of Madrid, Association of Medicine and Surgery of San Carlos of Madrid, Central University). She highlights the series of documents and its most representative documents with the information they offer in relation to the investigation. The article closes with an annex containing a search model of the information relating to Navarra in the aforementioned section.
Keywords: National Historical Archive; Documentary Ressources; Navarre; Educational Establishments; University of Alcalá; Central University; Saint Charles College of Medicine